2017
DOI: 10.1136/bmjopen-2017-016095
|View full text |Cite
|
Sign up to set email alerts
|

The Indigenous Counselling and Nicotine (ICAN) QUIT in Pregnancy Pilot Study protocol: a feasibility step-wedge cluster randomised trial to improve health providers' management of smoking during pregnancy

Abstract: IntroductionIndigenous women have the highest smoking prevalence during pregnancy (47%) in Australia. Health professionals report lack of knowledge, skills and confidence to effectively manage smoking among pregnant women in general. We developed a behaviour change intervention aimed to improve health professionals’ management of smoking in Indigenous pregnant women—the Indigenous Counselling And Nicotine (ICAN) QUIT in Pregnancy. This intervention includes webinar training for health professionals, an educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Out of the 20 studies reviewed, ten (50%) of them reported outcomes related to intervention effectiveness ( 1 , 34 , 36 , 38 , 40 , 41 , 45 , 48–50 ). There were several studies where the primary outcome was tobacco cessation [ n = 7; ( 32 , 36 , 38 , 45 , 47–49 )]. In a tobacco cessation program for pregnant Aboriginal women, self-reported 12-week 7-day point-prevalence abstinence was 13.6% ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 20 studies reviewed, ten (50%) of them reported outcomes related to intervention effectiveness ( 1 , 34 , 36 , 38 , 40 , 41 , 45 , 48–50 ). There were several studies where the primary outcome was tobacco cessation [ n = 7; ( 32 , 36 , 38 , 45 , 47–49 )]. In a tobacco cessation program for pregnant Aboriginal women, self-reported 12-week 7-day point-prevalence abstinence was 13.6% ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sixty percent of the studies described processes and outcomes related to Adoption [ n = 12; ( 1 , 32 , 36–38 , 40–42 , 44 , 47–49 )]. At the staff level, authors highlighted strategies, for and barriers to, Adoption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The iSISTAQUIT program has been adapted from foundation work established by a pilot project called ICAN (Indigenous Counselling and Nicotine) QUIT in Pregnancy (Phase 2) that was developed and trialled in six Aboriginal Community-Controlled Health Organisations (ACCHOS) with the aim of training HCPs in culturally sensitive smoking cessation assistance to pregnant Aboriginal and Torres Strait Islander women who smoke, [28][29][30] as well as the SISTAQUIT Randomised Controlled Trial (Phase 3) [31]. This is intervention built on extensive formative research into pregnant Aboriginal and Torres Strait Islander women who smoke and health professional delivery of smoking cessation care [10,[32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%